2018
DOI: 10.1016/j.indcrop.2017.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of peat moss with softwood biochar for soil-free marigold growth

Abstract: A B S T R A C TPeat moss has historically been a key component of soil-free substrates in the greenhouse and nursery industries. However, the increasing expense of peat, negative impacts of peat mining on wetland ecosystems, and growing perception of peat as unsustainable have led to investigation for alternatives. Biochar (BC) is a promising substitute for peat, yet the majority of studies examine additions of BC to peat-based substrates rather than replacing the peat component or employ relatively low substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 85 publications
3
35
0
Order By: Relevance
“…The reason was that the incorporation of superabsorbent polymer increased the porosity and water-holding capacity and also effectively prevented an excessive increase of pH and EC at the high biochar rates [70]. Margenot et al [62] also showed that mixes with 10%, 20%, 30%, 40%, 50%, 60% or 70% softwood biochar and 30% perlite with the rest being peat (by vol.) led to similar seed germination and plant height compared to control (mixes with 30% perlite and 70% peat by vol.).…”
Section: Other Substrate Components Mixed With Biochar In Container Smentioning
confidence: 99%
“…The reason was that the incorporation of superabsorbent polymer increased the porosity and water-holding capacity and also effectively prevented an excessive increase of pH and EC at the high biochar rates [70]. Margenot et al [62] also showed that mixes with 10%, 20%, 30%, 40%, 50%, 60% or 70% softwood biochar and 30% perlite with the rest being peat (by vol.) led to similar seed germination and plant height compared to control (mixes with 30% perlite and 70% peat by vol.).…”
Section: Other Substrate Components Mixed With Biochar In Container Smentioning
confidence: 99%
“…Another research was conducted and wood chips and straw were applied in the soil and the results showed that nitrogen mineralization and nitrification rates were higher significantly in the soil-applied wood chips. The bad thing is that when we applied wood chips in the soil, nitrogen deficiency occurs and then an additional supplement of nitrogen is required [89]. Carbon contents of early woods are higher than late woods [90].…”
Section: Wood Chipsmentioning
confidence: 99%
“…Dispenza et al [18] reported that incorporation of conifer BC (60% or 80% by volume) in a brown peat-based substrate increased the dry weight and canopy height of potted Euphorbia × lomi plants due to improved physiochemical characteristics of the substrate. Margenot et al [19] found that softwood BC in a soilless substrate can completely replace peat at 70% (v/v) without pH adjustment for producing containerized marigold. Similarly, Guo et al [20] demonstrated that pinewood BC produced at 450 • C can be used in a peat-based substrate for up to 80% (v/v) without negative effects on the growth and development of containerized Easter lily (Lilium longiflorum).…”
Section: Introductionmentioning
confidence: 99%